Hubungan Antara Self-Efficacy dengan Self-Esteem Bagi Graduate di Universitas dalam Mencari Pekerjaan - Sabar Analisis Zega; Ati Kusmawati (Lembaga Pengembangan Kinerja Dosen, 2024)
The need for self-efficacy and self-esteem is closely related to achieving success, especially in finding work after graduating from college. Because self-efficacy and self-esteem have an important role in increasing the stability of an individual's mental well-being. The background to the research is the difficult problem of finding work after graduating from college. In addition, undergraduate graduates often experience a decrease in self-esteem, self-confidence and do not fully believe in their abilities. This research aims to determine the level of relationship between self-efficacy and self-esteem for undergraduate graduates at universities in looking for work. This research uses quantitative correlational techniques with non-probability sampling using a purposive method. It is known that the population is 543 with a research sample of 85 respondents with a Slovin calculation precision of 10%. Data collection technique by distributing questionnaires via Google Form to 85 respondents. The results of this research show that there is a positive relationship between self-efficacy and self-esteem for university graduates who are looking for work, based on the Pearson correlation test of 0.231 and the coefficient interval score of 0.200-0.399, which is in the low category